Peran Kepemimpinan Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan Di RA Plus Dasussalam Bojonegoro - Fatimatuz Zuhriyyah Assyamsiyyah (Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the role of madrasah principal leadership in improving the quality of education at RA Plus Darussalam Bojonegoro. The research was conducted using a qualitative case study approach to gain an in-depth understanding of the phenomenon in its natural context. Data were collected through technique triangulation, namely participatory observation, in-depth interviews with the madrasah principal, teachers, and parents, as well as document studies. Data were analyzed interactively using the Miles and Huberman model (data reduction, data display, and conclusion drawing) with verification through source and method triangulation. The research findings indicate that the leadership role of the madrasah principal has been carried out optimally, encompassing roles as an educator, motivator, manager, administrator, supervisor, and entrepreneur. Quality improvement efforts were made through strategic planning based on self-evaluation, continuous teacher training, parenting class programs, and the development of institutional business units such as cooperatives and greenhouses. The results achieved include increased public interest, orderly administration, a conducive work climate, as well as improved teacher competence and parental understanding. It is concluded that the transformational leadership of the madrasah principal, supported by the synergy of all stakeholders, is the main key to sustainably improving the quality of education. This study recommends the need for continuous appreciation and support for madrasah principals and the strengthening of partnerships between schools and the community.